Geographische Forschung im Anschluss an Michel Foucault - Füller, Henning; Michel, Boris (Westfälisches Dampfboot, 2012)

Regionalforschung in der Geographie und interdisziplinäre area studies nach dem cultural turn: eine Einführung - Glasze, Georg; Füller, Henning; Husseini de Araújo, Shadia; Michel, Boris (Geographische Zeitschrift, 2014)
Geography beyond the cultural turn is inclined to understand regions merely as social or discursive constructs. Notwithstanding "regional specialisation" and "intimate regional knowledge", at least traditionally, play an important role in geography. Regional descriptors are still used to frame research questions and regional knowledge is considered to facilitate access to empirical data. Part of a current renaissance of area studies is a debate on a more procedural concept of regions beyond static (and often Eurocentric) denominators. However, this debate is still sparsely connected with regional geography and recent theoretical debates in social and cultural geography. This introduction and the three contributions of this special issue offer some impulses for such exchanges.
Keywords: Area studies; Cultural and social geography; Cultural turn; Regional geography

Shaping the Urban Renaissance: New-build Luxury Developments in Berlin - Marquardt, Nadine; Füller, Henning; Glasze, Georg; Pütz, Robert (Urban Studies, 2013)
Inner-city living is a hot topic in Germany. Policy-makers long for new middle- and upper-class residents; evidence of urban in-flight has been documented by scholars, and debates on reurbanisation are in full swing. This trend has also led to the emergence of a new housing product in German metropolises: high-priced, centrally located and newly built apartment and townhouse developments. In this paper, these luxury developments are analysed as part of a general process of urban restructuring and a focus is on the contradictions inherent to the idea of urbanity taking shape here. Guided by Foucault's governmentality approach, new luxury developments are understood as a powerful reworking of how the city, its uses and users are imagined and governed. In doing so, the paper aims to show that the concept of governmentality enables a critique of current processes of urban restructuring that may enrich the on-going debates on gentrification. © 2012 Urban Studies Journal Limited.

Sicherheit, Prävention und Verortung - Füller, Henning; Glasze, Georg (Geographische Rundschau, 2014)

'Stop Being a Tourist!' New Dynamics of Urban Tourism in Berlin-Kreuzberg - Michel, Boris; Füller, Henning (International Journal of Urban and Regional Research, 2014)
Berlin is witnessing a massive tourism boom, and parts of it can be described as 'new urban tourism', which shows a preference for off the beaten track areas and 'authentic' experiences of the city. This form of tourism seems especially salient in Kreuzberg. It is here that an openly articulated critique of tourism attracted national attention in 2011 and has not ceased to do so since. This article aims to better understand the conflictive potential of (new urban) tourism in Kreuzberg. We argue that the readily expressed negative attitudes against tourists and the easily accepted link between tourism and gentrification have to be explained against the backdrop of certain housing-market dynamics. Rising rents and a diminution in the number of flats available for rent are fuelling fears of gentrification in Kreuzberg, while the interest shown in new urban tourism and the comparatively low-priced real-estate market in Berlin result in a growing number of holiday flats. Although adding only slightly to the tightening of the housing market, holiday flats render complex processes of neighborhood change visible and further sustain an already prevalent tourism critique. © 2014 Urban Research Publications Limited.
Keywords: Authenticity; Berlin; Gentrification; Germany; Housing market; Tourism

Tourismus - Michel, Boris; Beurskens, Kristine; Bürk, Thomas; Füller, Henning; Grube, Nils (Handbuch Kritische Stadtgeographie, 2018)

Wissenschaftlich Arbeiten: Recherchieren, Produzieren, Präsentieren / Autoren: Henning Füller, Georg Glasze, Klaus Geiselhart, Christoph Haferburg, Thomas Hübner und Florian Weber. 2., bearb. Aufl. Erlangen 2011 - Glasze, Georg; Geiselhart, Klaus; Hübner, Thomas; Haferburg, Christoph; Füller, Henning; Weber, Florian (Institut für Geographie, 2011)
UnivIS-Import:2015-04-15:Pub.2010.nat.dgeo.IG.LGIPDK.wissen

Wissenschaftlich Arbeiten : Recherchieren, Produzieren, Präsentieren / Autoren: Matthias Braun, Henning Füller, Georg Glasze, Klaus Geiselhart, Christoph Haferburg, Thomas Hübner und Florian Weber. 3., aktual. Aufl. Erlangen 2012 - Füller, Henning; Hübner, Thomas; Braun, Matthias; Glasze, Georg; Geiselhart, Klaus; Haferburg, Christoph; Weber, Florian (Institut für Geographie, 2012)

Wissenschaftlich Arbeiten : Recherchieren, Produzieren, Präsentieren / Bearb. der vorlieg. Aufl.: Thomas Hübner. Autoren: Henning Füller, Klaus Geiselhart, Georg Glasze, Christoph Haferburg und Thomas Hübner. 4., neu bearb. Aufl. Erlangen 2021 - Hübner, Thomas; Glasze, Georg; Füller, Henning; Geiselhart, Klaus; Haferburg, Christoph (Institut für Geographie, 2021)

«Σταμάτα να είσαι τουρίστας!» Η νέα δυναμική του αστικού τουρισμού στο Kreuzberg του Βερολίνου - Füller, Henning; Michel, Boris (Kaboom, 2018)